THE ROLE OF NATIONAL MUSICAL INSTRUMENTS IN KARAKALPAK FOLKLORE: A CULTURAL AND MUSICAL EXPLORATION (European Journal of Interdisciplinary Research and Development, 2025)
Karakalpak folklore is a vibrant oral tradition rooted in the epic narratives, communal rituals, and historical memory of a people living on the fringes of the Aral Sea. Central to this heritage are the national musical instruments, which not only provide the sonic backdrop for storytelling and ritual but also embody the cultural identity and resilience of the Karakalpak community. This article examines the historical evolution, performance practices, and symbolic significance of traditional Karakalpak musical instruments within the context of folklore. By analyzing the roles of stringed, percussion, and wind instruments, the discussion reveals how these sonic tools serve as active agents in shaping narrative structure, emotional expression, and social cohesion. Finally, the article considers contemporary challenges and efforts in preserving these traditions in a modern world.